Penguatan Ketahanan Keluarga melalui Kolaborasi Lintas Sektor : Studi Kasus di Kemantren Danurejan, Kota Yogyakarta - Siskasari, Agista; Hermawati, Istiana (Journal of Indonesian Rural and Regional Government, 2025)
This study examines strategies for strengthening family resilience in Danurejan District, Yogyakarta City, through a collaborative governance approach. Family resilience is understood as the ability of families to survive and adapt to economic, social, and cultural challenges. Using a descriptive qualitative method, data were collected through in-depth interviews, participatory observation, and documentation studies. The findings show that collaboration between the government, social institutions, and the community plays a crucial role in strengthening family resilience. Community-based programs such as posyandu (integrated health posts), family economic training, and citizen communication forums have proven effective in enhancing social, economic, and psychological resilience. This study contributes to the development of the collaborative governance model as a sustainable strategy for strengthening family resilience in urban areas. The practical implications of these findings highlight the need for strengthening cross-sectoral collaboration and revitalizing communication forums as efforts to build resilient and harmonious families amidst urban social dynamics.